Orientasi Psikologi Pendidikan Islam di Sekolah dan Prasekolah - Ika Hariani (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
This paper contains the psychology orientation of Islamic education. Each education level is different in how to educate and how to overcome the problems that occur, the age of the kindergarden is different from elementary school age, as well as elementary schools are different teaching systems with secondary schools, and also level schools. middle school is different in how to teach and how to deal with the problem with upper level schools. All levels have a phase that must be passed as an educator, if the wrong application results in misorientation, or lose direction. So that education is only a formality without any spirit that shapes the ethics of students to become human beings who are desired by Islamic education itself. The success of education depends on the initial orientation of the establishment of an educational institution. Where students will be taught at the institution. There is a lot of moral degradation in education because the empty psychology orientation of Islamic education in educational institutions, if there is an Islamic name is only a label without content, if from the beginning the educational institution has lost its orientation.